SGLT2i use is associated with reduced risks of cardiopulmonary inflammatory complications in cancer patients with diabetes: a retrospective cohort study - Li, Dan; Li, Yanlin; Meng, Lingyu; Yu, Xin; Jiao, Min (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChronic low-grade inflammation constitutes a shared pathological mechanism linking type 2 diabetes mellitus (T2DM) and malignancies. While preclinical evidence suggests SGLT2 inhibitors (SGLT2i) may attenuate chronic inflammation, clinical data regarding their protective effects against multi-system inflammatory complications during anti-tumor therapy remain scarce.ObjectiveThis study examined the association between SGLT2i use and the risk of cardiopulmonary inflammatory complications following anti-tumor therapy in cancer patients with diabetes.MethodsWe conducted a retrospective, propensity score-matched cohort study at the First Affiliated Hospital of Xi'an Jiaotong University. Patients diagnosed with T2DM and cancer between March 2017 and March 2024, who survived over one year after initiating anti-tumor therapy, were included. Participants were stratified into SGLT2i users and non-users based on pre-treatment exposure. Non-SGLT2i users were matched 1:1 to users by age, sex, cancer stage, hemoglobin A1c (HbA1c), and estimated glomerular filtration rate (eGFR) levels. The primary outcome was a composite of cardiopulmonary inflammatory complications (pneumonia, pleural effusion, and pericardial effusion).ResultsAmong 1,183 eligible patients with T2DM and cancer, 103 received SGLT2i before anti-tumor therapy (SGLT2i group) and were matched with 103 non-SGLT2i users. Over the median follow-up period of 48 months, the SGLT2i group had a significantly lower risk of composite events (15.53% vs. 35.92%, p = 0.002) than the non-SGLT2i group, with reduced risks for pneumonia (9.71% vs. 22.33%, p = 0.030), pleural effusion (5.83% vs. 17.48%, p = 0.025), and pericardial effusion (2.91% vs. 10.68%, p = 0.030).ConclusionIn cancer patients with diabetes, pre-treatment SGLT2i use is associated with reduced risks of cardiorespiratory inflammatory complications. Robust prospective studies are warranted to confirm the role of SGLT2i in mitigating multi-system inflammatory risks in this cohort.